2021
DOI: 10.1155/2021/9944880
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Empagliflozin and Gemigliptin on LPS-Stimulated Macrophage via the IKK/NF-κB, MKK7/JNK, and JAK2/STAT1 Signalling Pathways

Abstract: Background. Sodium-glucose cotransporter 2 (SGLT2) and dipeptidyl peptidase-4 (DPP-4) inhibitors are glucose-lowering drugs whose anti-inflammatory properties have recently become useful in tackling metabolic syndromes in chronic inflammatory diseases, including diabetes and obesity. We investigated whether empagliflozin (SGLT2 inhibitor) and gemigliptin (DPP-4 inhibitor) improve inflammatory responses in macrophages, identified signalling pathways responsible for these effects, and studied whether the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 66 publications
(70 reference statements)
0
56
2
1
Order By: Relevance
“…It is well documented that the intracellular effectors of empagliflozin include extracellular signal-regulated kinase 1/2 [ 65 ], phosphoinositide 3-kinase/Akt [ 18 ], transforming growth factor β1 [ 66 ], nuclear factor κB [ 67 ], Janus kinase 2 [ 67 ], Sirtuin 1 [ 68 ], hypoxia inducible factor 1α [ 69 ], protein kinase G Iα [ 70 ], heme oxygenase 1 [ 71 ], peroxisome proliferator-activated receptor gamma coactivator 1α [ 72 ] and AMPKα1 [ 20 ]. Among them, AMPK has been identified as an indispensable inducer of mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the intracellular effectors of empagliflozin include extracellular signal-regulated kinase 1/2 [ 65 ], phosphoinositide 3-kinase/Akt [ 18 ], transforming growth factor β1 [ 66 ], nuclear factor κB [ 67 ], Janus kinase 2 [ 67 ], Sirtuin 1 [ 68 ], hypoxia inducible factor 1α [ 69 ], protein kinase G Iα [ 70 ], heme oxygenase 1 [ 71 ], peroxisome proliferator-activated receptor gamma coactivator 1α [ 72 ] and AMPKα1 [ 20 ]. Among them, AMPK has been identified as an indispensable inducer of mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model, depletion of STAT-1 activation significantly reduced synaptic dysfunction and cognitive impairment associated with Tau accumulation [ 88 ]. Empagliflozin was proven to mitigate inflammation by downregulation of the JAK2/STAT1 pathway in macrophages [ 89 ]. Macrophages take part in cognitive impairment as perivascular macrophages (PVM) are the source of vascular oxidative stress by producing a large amount of free radicals near the neurovascular unit [ 90 ].…”
Section: Inflammationmentioning
confidence: 99%
“…It was previously reported that empagliflozin could exhibit an anti-inflammatory effect through SGLT-2-independent mechanisms, including intracellular activation of AMPK, attenuation of superoxide production, and the suppression of oxidative stress ( Zhou et al, 2018 ). Additionally, it showed an anti-inflammatory effect via the inhibition of NF-κB/JNK/STAT signaling pathways ( Lee et al, 2021 ). Its suppressive effect on NFκB showed an anti-inflammatory cardioprotective effect in patients subjected to doxorubicin ( Quagliariello et al, 1894 ).…”
Section: Introductionmentioning
confidence: 99%